Factors Associated with Olfactory and Gustatory Dysfunction in Post-COVID-19 Patients Treated at a Peruvian Hospital - Fernández, Mirian (2025)
To determine the association between sociodemographic, epidemiological, and clinical factors and olfactory-gustatory dysfunction (OGD) in post-COVID-19 patients treated at a Peruvian hospital. An observational, analytical, and cross-sectional study was conducted using the clinical records of adult patients treated for COVID-19 at the Hospital Militar Central (HMC) between July 2020 and December 2022. Data were collected in person using a structured form that recorded sociodemographic, epidemiological, and clinical variables, as well as the presence of OGD. Poisson regression with robust variance was performed using SPSS v25. A total of 237 post-COVID-19 patients were included. Of these, 53.2% presented OGD. Among those with dysfunction, 81% reported both olfactory and gustatory impairment, 12.7% reported olfactory impairment only, and 6.3% reported gustatory impairment only. Multivariate analysis revealed that age under 60 years (p=0.007; RPa=1.194), female sex (p=0.005; RPa=1.160) and having “other” comorbidities (p=0.027; RPa=1.214) were significantly associated and increased the prevalence of OGD. Patients with age age under 60 years, female sex and  with other comorbidities were significantly associated with olfactory-gustatory dysfunction.